The University of the Philippines Institute of Library Science curriculum and the needs of business and industry - Ouano, Val Rico Rommel G.; Santos, Herminia H. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1998)
This study deals with the University of the Philippines Institute of Library Science curriculum and how relevant and useful its courses are in the performance of librarians and information professionals in a special library. The special libraries chosen are in 50 private business and industry corporations in Makati City.
Two sets of questionnaires were distributed; one for personnel managers and another for 25 librarians who were graduates of ILS since 1979. Only 25 librarians in the 50 corporations were surveyed as they seemed to be a good source of feedback with regards to the ILS curriculum being graduates of the BLS program.
Results show that personnel managers don't really look for special librarians who specialize in a specific task or duty. They would rather want an applicant who knows every aspect in the field of librarianship. Tasks they usually assign to librarians are cataloging and reference service. Being computer literate is also an advantage.
The graduates of U.P. ILS believe that they were well prepared to perform their respective duties in a special library. All the needed skills were taught to them during their four years in the Institute.
Computer print out.
Vita.
Thesis (Bachelor of Library Science)--University of the Philippines Diliman
Keywords: Library science -- Curricula. -- Philippines; University of the Philippines. Institute of Library Science -- Graduate students; Special libraries -- Philippines -- Makati City